Euro–Meso–Macro: the New Regions in Iberian and European Space - Medeiros, Eduardo (2017)
The European integration process, which has been supported by European Cohesion Policy since the end of the 1980s, is witnessing the establishment of an increasingly large number of the so-called Euroregions and similar structures, mainly as a result of experiments and projects carried out under the INTERREG community initiative, in all its strands (cross-border, transnational and interregional cooperation), in a quest to search for better adequate socioeconomic development and multilevel governance solutions. This article explores the emergence of these new governance spaces in Europe and, in particular, in the Portuguese–Spanish border area, and it aims to assess their contribution of injecting new tailor-made regional/local development strategies and also to provide a conceptual clarification of these spaces, which became more relevant with the advent of the Macro-Regions that have come into being since 2007.